Application of AI Technologies in Teaching ESL and ESP at Agro-Technical Higher Educational Institutions - Zoriana Dziubata (Pedagogical Discourse, 2024)
The paper is aimed to contribute to lectures’ AI readiness and their understanding of potential benefits and drawbacks of AI technologies in order to integrate AI (namely, ChatGPT) into language education. The study offers recommendations on practical application of AI in teaching English as a Second language (ESL) and English for Specific Purposes (ESP) at agro-technical higher educational institutions, namely on localizing content, personalizing materials, developing specific language skills and soft-skills, introducing profession-specific learning materials and creating a comfortable learning environment. It discusses the impact of AI on language teaching, including its problems, concerns (plagiarism, bias, ethics, inequalities) and the ways it can transform language teaching and learning practices on condition of providing the AI readiness of both educators and learners.